Taxation and economic growth in the European Union: a quantile approach - Blanco, Francisco; Delgado, Francisco J. (Revista de Economía Mundial, 2019)
The available literature on the relationship between taxation and economic growth is mixed, although some consensus exists on the negative effects of some taxes on growth. In this paper we study the relationship between taxation and growth for the European Union in 2004?2016 through a quantile regression approach to detect different patterns along the distribution. The results show a negative effect of the tax burden, with higher impact at the last quantiles, evidencing a non-linear relationship between tax burden and economic growth in the European Union. In contrast, the top corporate tax rate appears as non-significant in this study. In addition, population growth, with negative impact, and investment and human capital, with positive effect, also explain the economic growth in the period.